Genetic Variation Analysis of Four Local Varieties of Indonesian Black Rice (Oryza sativa L.) Based on Partially rbcL cpDNA Gene Sequence - Basith, Abdul; Arumingtyas, Estri Laras; Widodo, Widodo (Graduate School, Universitas Brawijaya, 2021)
Black rice (Oryza sativa L.) varieties i.e. Toraja (South Sulawesi), Cempo Ireng (Yogyakarta), Wojalaka (East Nusa Tenggara), and Manggarai (East Nusa Tenggara) are four local black rice varieties in Indonesia whose character has not been widely studied, especially the character of genetic variation. Research aimed to determine the variation of the rbcL gene in the four local black rice varieties. The sample for testing the variation of the rbcL gene sequence in the form of black rice leaves six weeks after planting. Dendogram was carried out using the UPGMA method with the Kimura 2-parameter algorithmic calculation model using the MEGA5 version 5.2.2 program. The results showed that partially the rbcL gene sequence was successfully amplified on four black rice varieties with a sequence length of 487 bp. The partial rbcL sequence of black rice consisted of 26.58% tyrosine, 21.38% cytosine, 28.86% adenine, and 23.18% guanine. The value of G + C content was 0.446, with the frequency of invariable sites of 97.13%. The frequency of informative parsimony sites was 1.43% with a nucleotide diversity (Pi) value of 42-10, the number of haplotypes was 5, and the total number of mutations and polymorphic sites was 14. The ratio between transition and transversion (ts/tv ratio k) for purine bases was 1.741 and pyrimidine was 3.571, with the estimated overall ratio between transition and transversion (R) of 1.31. Based on the dendogram, the farthest genetic distance was found in Wojalaka and Manggarai varieties, which were 0.019 respectively.Keywords: black rice, genetic variation, local varieties, rbcL gen